The haunting [videorecording (DVD)] - Wise, Robert, 1914-2005; Wise, Robert, 1914-2005; Harris, Julie, 1925-2013; Bloom, Claire, 1931-; Tamblyn, Russ; Jackson, Shirley, 1916-1965 (Warner Home Video, 2010)
A parapsychologist and two mediums spend a weekend in a haunted mansion.